2021
DOI: 10.3390/jcm10071355
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Performance of a Self-Operated Home Monitoring System for Early Detection of Neovascular Age-Related Macular Degeneration

Abstract: The real-world performance of a home telemonitoring strategy (ForeseeHome AMD Monitoring System®, Notal Vision, Inc.,Manassas VA, USA) was evaluated and compared to the device arm of the AREDS2-HOME study among patients with intermediate AMD (iAMD) who converted to neovascular AMD (nAMD). All patients with confirmed conversion to nAMD who used the home monitoring system from 10/2009 through 9/2018 were identified by Notal Vision Diagnostic Clinic’s medical records. Selected outcome variables were evaluated, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 34 publications
2
13
0
Order By: Relevance
“…One promising aspect of OCT technology that may dramatically increase the amount of available data, and clinical utility, is its emerging portability. Options for at home self-administered OCT imaging are already under investigation (47,48). The clinical goals of at home testing include early detection of disease through screening, closer monitoring of active disease progression, and a reduction in the number of necessary in-person clinical visits.…”
Section: Discussionmentioning
confidence: 99%
“…One promising aspect of OCT technology that may dramatically increase the amount of available data, and clinical utility, is its emerging portability. Options for at home self-administered OCT imaging are already under investigation (47,48). The clinical goals of at home testing include early detection of disease through screening, closer monitoring of active disease progression, and a reduction in the number of necessary in-person clinical visits.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of predicting the conversion to exudative AMD within 2 years is that it can impact the development of follow-up and monitoring schedules for a patient and for potentially selecting a higher-risk group of patients who may benefit from more expensive home-monitoring strategies. (Busquets and Sabbagh 2021) (Ho et al 2021) (Pershing and Stein 2017) A personalized monitoring approach could potentially allow earlier detection of these patients, thereby leading to earlier therapeutic intervention and better visual outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Ensuring regular and reliable device usage is essential when implementing home monitoring of disease activity. Although there have been positive reports of long-term compliance [ 16 ], large non-proprietary studies of the ForeseeHome device have shown significant underutilisation in the general population compared to the initial study cohorts, with up to a quarter of patients ceasing usage within 1 year [ 17 ]. Regular imaging would be essential if home monitoring becomes the primary method of disease surveillance.…”
Section: Barriers and Future Challengesmentioning
confidence: 99%